Akar-Akar Filsafat Ekonomi Dalam Pemikiran Klasik Islam : Relevansi Al-Ghazali Dan Ibn Khaldun Bagi Ekonomi Kontemporer - Saputra, Ega; Iska, Syukri; Hidayati, Azifah; Marlion, Fandi Ahmad; Zeki, Ibnu (JPSDa: Jurnal Perbankan Syariah Darussalam, 2026)
Modern Islamic economics is often criticized for being too reactive, technical, and lacking an original philosophical foundation. This study aims to fill this gap by exploring the philosophical roots of Islamic economics through the thoughts of two classical figures, namely Imam Al-Ghazali and Ibn Khaldun. This study is a descriptive qualitative research type using the library research method and the philosophy of the history of thought approach, which analyzes the main works of these two thinkers, namely I?y?’ ‘Ul?m al-D?n (Al-Ghazali) and Al-Muqaddimah (Ibn Khaldun). The results of the study show that Al-Ghazali developed a teleological-normative economic philosophy that emphasizes economic activity as a means to achieve purification of the soul (tazkiyat al-nafs) and happiness in the afterlife. Key concepts include: economics as a means (was?lah), ma?la?ah as a regulative principle, and strict ethics in production, exchange, and consumption. Meanwhile, Ibn Khaldun developed an empirical-sociological economic philosophy based on historical observation, focusing on the dynamics of civilization (‘umr?n), the theory of dynastic cycles, the value of labor, and the role of the state in economic development. This article concludes that a reactualization of this classical thinking can enrich the philosophical foundation of modern Islamic economics, making it more robust and contextual.